2014
DOI: 10.11606/issn.2318-3659.v51i1p30-36
|View full text |Cite
|
Sign up to set email alerts
|

Influência de diferentes dietas com alto teor de concentrados sobre parâmetros ruminais, bioquímicos e urinários de ovinos

Abstract: ResumoOito ovinos, da raça Santa Inês, receberam dieta controle (C) (80% de feno de capim coast-cross e 20% de concentrado comercial) e em seguida foram submetidos a experimento em quadrado latino com dietas contendo 30% desse feno e 70% dos concentrados: polpa cítrica peletizada (PCP); polpa cítrica farelada (PCF); fubá de milho (FM) e farelo de trigo (FT). Depois de 21 dias de adaptação às dietas, foi realizada monitoração visual por 24 h. No dia subsequente à observação, na terceira hora após a alimentação,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…After the initial reduction of ruminal pH, similar to dairy cattle induced to SARA (Steele et al, 2011), this variable showed fluctuation, possibly because the long-term, high-grain diet increased HCO 3 − secretion into the reticulo-rumen (Gäbel et al, 1991), and propionate, butyrate, and lactate absorption in the rumen (Schwaiger et al, 2013). The decrease of urine pH, as observed in sheep fed 70% concentrate feed (Minervino et al, 2014), indicates regulation of metabolic acidosis caused by SARA, since the small lung capacity of ruminants requires acid elimination via the kidneys (Enemark et al, 2002), and renal HCO 3 − retention and acid excretion are necessary for long-term correction of metabolic acidosis (Houpt, 2006;Carlson, 2009;Jones, 2010). The ruminal pH above SARA limits (Owens et al, 1998;Enemark et al, 2002;Kleen et al, 2003) does not exclude its occurrence, because further parameters are required to diagnose it (Brossard et al, 2003), as exemplified by ruminal fluid characteristics and urinary pH.…”
Section: Discussionmentioning
confidence: 87%
“…After the initial reduction of ruminal pH, similar to dairy cattle induced to SARA (Steele et al, 2011), this variable showed fluctuation, possibly because the long-term, high-grain diet increased HCO 3 − secretion into the reticulo-rumen (Gäbel et al, 1991), and propionate, butyrate, and lactate absorption in the rumen (Schwaiger et al, 2013). The decrease of urine pH, as observed in sheep fed 70% concentrate feed (Minervino et al, 2014), indicates regulation of metabolic acidosis caused by SARA, since the small lung capacity of ruminants requires acid elimination via the kidneys (Enemark et al, 2002), and renal HCO 3 − retention and acid excretion are necessary for long-term correction of metabolic acidosis (Houpt, 2006;Carlson, 2009;Jones, 2010). The ruminal pH above SARA limits (Owens et al, 1998;Enemark et al, 2002;Kleen et al, 2003) does not exclude its occurrence, because further parameters are required to diagnose it (Brossard et al, 2003), as exemplified by ruminal fluid characteristics and urinary pH.…”
Section: Discussionmentioning
confidence: 87%
“…Louvandini and Vitti [38], in a metabolic assay, provided different daily levels of phosphorus for sheep (1, 2, and 3 g/animal) and verified a relation of r = 0.90 between the phosphorus absorbed and the phosphorus consumed. According to Minervino et al [39], the greater presence of phosphorus in the diet reflects a higher blood concentration. Thus, the phosphorus in the dietary ingredients, especially corn, may have caused this increase in addition to time.…”
Section: Discussionmentioning
confidence: 99%
“…11821, following the technique described previously (Fossati et al 1980). Urinary concentrations (urea, allantoin, and uric acid) were corrected by the concentration of urinary creatinine and the metabolic weight (live weight 0.75 ) of the animals, using the following formula: Concentration of the metabolite in question (mmol/L) × metabolic weight/urinary creatinine concentration (mmol/L) (Minervino et al 2014a).…”
Section: Methodsmentioning
confidence: 99%